Pengembangan Permainan Bola Berantai Voli Dalam Pembelajaran Penjasorkes Siswa SMP Kecamatan Gringsing - Andaru Krisna Jati; Agus Raharjo; Harry Pramono; Bhayu Billiandri (Indonesian Journal for Physical Education and Sport, 2024)
The main problem faced is the lack of students' lower and upper passing skills in volleyball. This study aims to develop an effective ‘Volleyball Chain Ball Game’ model in volleyball learning. This research is a type of development research using 10 stages of research based on instructions derived from Sugiyono's sources. Data collection techniques were carried out through questionnaires and interviews. Based on the results of the analysis, the development of the volleyball chain ball game was declared feasible to use. This is based on the results of the large-scale test which obtained a total percentage of 88.94%, which is in the ‘Very Good’ category. Thus, this volleyball chain ball game is feasible and can be implemented in learning PE at Junior High Schools.